Aktivitas Berbagi Pengetahuan Dalam Meningkatkan Literasi Fisik Anak Usia Dini Studi Kasus di motoricshool Halo Kids Indonesia - Arindi, Metri; Rachmawati, Tine Silvana; Perdana, Fitri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to explain how knowledge-sharing activities occur at Halo Kids Indonesia, identify its impact on children's physical literacy, and identify the knowledge sharing process. The qualitative method is used with a case study approach, involving data collection through relevant informants, and the data is presented in narrative form. This research shows that Halo Kids Indonesia applies the concept of sharing knowledge effectively through the stages of socialization, externalization, combination, and internalization. Activities such as sharing parenting, visual documentation, and training play an essential role in children's physical literacy development. In conclusion, Halo Kids Indonesia successfully applies knowledge sharing to increase physical literacy in early childhood. Keywords: Knowledge Sharing, Physical Literacy, Early Childhood, Motor Training